Structural insights into the PrpTA toxin–antitoxin system in Pseudoalteromonas rubra - Wang, Chenchen; Niu, Chuanying; Hidayatullah, Khan Muhammad; Xue, Lu; Zhu, Zhongliang; Niu, Liwen (Frontiers in Microbiology, 2022)
Bacteria could survive stresses by a poorly understood mechanism which contributes to the emergence of bacterial persisters exhibiting multidrug tolerance (MDT). Recently, Pseudoalteromonas rubra prpAT module was found to encode a toxin PrpT and corresponding cognate antidote PrpA. Here, we reported firstly multiple individual and complex structures of PrpA and PrpT, which uncovered the high-resolution three- dimensional structure of the PrpT:PrpA2:PrpT heterotetramer with the aid of SEC-MALS. And PrpT:PrpA2:PrpT is composed of a PrpA homodimer and two PrpT monomers which are relatively isolated from each other and from ParE family. The superposition of antitoxin monomer structures from these structures highlighted the flexible C-terminal domain (CTD). And a striking conformational change in the CTDs of PrpA homodimer depolymerized from homotetramer was provoked upon PrpT binding, which accounts for the unique PrpT-PrpARHH mutual interactions and further neutralizes the toxin PrpT. PrpA2-54-form Ⅰ and Ⅱ crystal structures both contain a doughnut-shaped hexadecamer formed by eight homodimers organized in a cogwheel-like form via inter-dimer interface dominated by salt bridges and hydrogen bonds. Moreover, PrpA tends to exist in solution as a homodimer other than a homotetramer (SEC-MALS) in the absence of flexible CTD. Actually, multiple multi-dimers, tetramer and hexamer included, of PrpA2-54 mediated by the symmetric homodimer interface and the complicated inter-dimer interface could be observed in solution. SEC-MALS assays highlighted that phosphate buffer (PB) and the increase in the concentration appear to be favorable for the PrpA2-54 oligomerization in solution. Taken together with previous research, a model of PrpA2-54 homotetramer in complex with prpAT promoter and the improved mechanism underlying how PrpTA controls the plasmid replication were proposed here.